A arte, o urbano e o social: um espaço de provocação (Palíndromo, 2014)
Contemporary artists, aiming launching provocations, play with ambiguity and alterity in their production to discuss elements of the visual arts’ system itself - the figure of the artist, the museum, the cultural journalism, etc. In dialogue, we analyze the projects of artists such as Yuri Firmness (with his “invented artist” Souzousareta Geijutsuka) and Bruno Moreschi (with his project ART BOOK, where he creates an encyclopedia of art with 50 fictional artists designed by him). In this context, the re- search involves the practical development of the persona of a “technological artist” - a chatbot that pretends to be an artist acting in a “teleperformance” on the Internet - supposedly introducing a “direct” relationship between artist and audience.
Keywords: art; urban; intervention